Condutas tomadas pelos enfermeiros, relacionadas ao procedimento de sondagem vesical - Alves, Maria Virgínia Martins Faria Faddul [UNESP]; Luppi, Claudia Helena Bronzato [UNESP]; Paker, Cybelle [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
Introduction: Urinary tract infection (UTI) is an inflammation of the urinary passages with associated symptoms and the presence of bacteria in the urine. UTI is responsible for 35 to 45% of all hospital infections (HI) acquired. The great majority of these cases, 80% of UTI, are related to vesicle catheterization, and among hospitalized patients, 10% are exposed to this procedure (RODRIGUES, 1997). Objective: The principal aim of this work is to identify epidemiological aspects of hospital infection occurrence and to verify preparations made by nurses of the inpatient units to control urinary infection.Material and Methods: The researcher collected the data through semistructured interviews, utilizing a questionnaire. 15 nurses, responsible for 15 infirmaries at the university hospital, were interviewed. This work was approved by the Committee of Ethics in Research - OF 272/20004 CEP. Principal results: It was verified that the most frequent topography was respiratory, in 42.1% of the cases, followed by communal and urinary infection, both in 15.8%, skin and soft parts in 10.5% of the responses; and posterior infection of the reproductive system, surgical site and peritoneal infection were each in 5.3% ofresponses. About 73.3% of the nurses knew the indices of hospital infection related to vesicular probing in their infirmary. The hospital has an active CCIH in various infirmaries, including notifying them in relation to infections. With regard to the aspects nurses considered most important to occurrence of urinary infection, 33.3% responded that duration of catheterization had a major influence; 21.2% held that errors in catheter manipulation collaborated to increase indices of infection and 18.2% reported that the gravity of the basic pathology of the patient aggravated the probing situation. The alternative measures utilized to prevent urinary infection were as follows: 29.7% of the nurses use constant evaluation of the catheter; another 29.7% employ a closed drainage system; 21.7% limit catheter use; 16.2% realize training of professionals and 2.7% responded that they orient the patient on intimate hygiene. Conclusions: Given what the nurses demonstrated, they are assuming some attitudes of prevention and adequate treatment as to the risks and benefits of the vesicular probing procedure, thus directing the individualization of nursing precautions. Furthermore, we can emphasize that preventive and alternative measures in catheter use are equivalent, since by utilizing alternative measures the nurse will be able to prevent UTI occurrence.

Introducción: La infección urinaria de tracto (UTI) es una inflamación de los pasajes urinarios con síntomas asociados a la presencia de bacterias en la orina. La UTI es responsable por el 35 a 45% de todas las infecciones adquiridas en los hospitales (IH). La mayor parte de estos casos, 80% de la UTI, está relacionada al cateterismo vesical. Entre pacientes hospitalizados el 10% es expuesto a este procedimiento (RODRIGUES, 1997). Objetivo: El objetivo principal de este trabajo es identificar los aspectos epidemiológicos de la ocurrencia de la infección adquirida en el hospital y verificar las medidas tomadas por los enfermeros de las unidades, para controlar la infección urinaria. Material y Método: la colecta de los datos por entrevistas semi estructuradas utilizó un cuestionario. Fueron entrevistados quince enfermeros responsables por las enfermerías del hospital universitario. Este trabajo fue aprobado por el Comité Ética de la Investigación - OF 272/20004 CEP. Resultados: Fue verificada que la topografía más frecuente fue la respiratoria, en 42,1% de los casos, seguido por la infección comunal y urinaria, en 15,8%, la piel y laspartes suaves en 10,5% de las respuestas; y por último la infección del sistema reproductor, lugar quirúrgico e infección peritoneal que también obtuvieron un 5,3% de respuestas. Cerca de 73,3% de los enfermeros sabían cuales eran los índices de la infección del hospital y lo relacionaban al sondaje vesicular en su enfermería. El hospital tiene un CCIH activo en varias enfermerías, incluso los mantiene informados sobre la relación de las infecciones. Con respecto a los aspectos que los enfermeros consideraron más importantes para la ocurrencia de la infección urinaria, 33,3% respondieron que la duración del cateterismoinfluenciaba enormemente; 21,2% consideraron que los errores en lamanipulación del catéter colaboraron en el aumento de los índices de la infección y 18,2% informaron que la gravedad de la patología básica del paciente agravaba el cuadro de sondaje. Las medidas alternativas utilizadas para prevenir la infección urinaria fueron: 29,7% de los enfermeros utiliza la evaluación constante del catéter; otros 29,7% emplea un sistema de drenaje cerrado; 21,7% hacen uso limitado del catéter; 16,2% dan instrucciones a los profesionales y 2,7% respondieron que ellos orientaban al paciente en la higiene íntima. Conclusiones: los enfermeros demostraron que ellos asumen algunas actitudes de prevención y demuestran conciencia en cuanto a los riesgos y los beneficios del procedimiento del sondaje vesical, así, muestran un avance en la individualización del cuidado de enfermería. Además, podemos destacar que las medidas de prevención y las medidas alternativas al uso del catéter equivalen, desde ya, a una forma de prevención de ocurrencia de UTI.

Introdução: A infecção do trato urinário (ITU) é inflamação das vias urinárias com sintomas associados e presença de bactérias na urina. A ITU é responsável por 35 a 45% de todas as infecções hospitalares (IH) adquiridas. A grande maioria dos casos, 80% de ITU, está relacionada com a cateterização vesical, e entre os pacientes hospitalizados 10% são expostos a este procedimento (RODRIGUES, 1997). Objetivo: identificar os aspectos epidemiológicos da ocorrência de infecção hospitalar e verificar as providências tomadas pelos enfermeiros das unidades de internação para controlar a infecção urinária. Material e Método: A coleta de dados foi realizada atravésde entrevista semi-estruturada, utilizando um questionário. Foram entrevistados 15 enfermeiros responsáveis pelas enfermarias do hospital universitário. Esta pesquisa foi aprovada pelo Comitê de Ética em Pesquisa - OF 272/20004 CEP. Resultados: Foi verificado que a topografia mais freqüente era a respiratória, com 42,1% dos casos, seguido da infecção comunitária e urinária, ambas com 15,8%, pele e partes moles com 10,5% das respostas e posteriormente infecção de sistema reprodutor, sítio cirúrgico e infecção peritoneal igualmente com 5,3% das respostas. Cerca de 73,3% dos enfermeiros sabiam quais eram os índices de infecção hospitalar relacionados a sondagem vesical de sua enfermaria. O hospital tem uma CCIH atuante nas diversas enfermarias, inclusive notificando-as em relação as infecções. Quanto aos aspectos que os enfermeiros consideravam mais importantes para a ocorrência da infecção urinária, 33,3% deles responderam que a duração da cateterização tinha uma grande influência; 21,2% consideraram que erros na manipulação do catetercolaboraram para aumentar os índices de infecção e 18,2% relataram que a gravidade da patologia de base do paciente agravava o quadro de sondagem. As medidas alternativas utilizadas para prevenir a infecção urinária foram que 29,7% dos enfermeiros estão fazendo uso de avaliação constante do cateter; outros 29,7% estão utilizando sistema de drenagem fechado; 21,7% utilizam a limitação do uso do cateter; 16,2% realizam treinamento dos profissionais e 2,7% responderam que orientavam o paciente sobre a sua higiene íntima.Conclusões: Os enfermeiros demonstraram que estão tomando algumas atitudes de prevenção e de tratamento adequados quanto ao risco e benefícios do procedimento de sondagem vesical, direcionando assim a individualização dos cuidados de enfermagem. Podemos destacar ainda que, as medidas de prevenção e as medidas alternativas ao uso do cateterismo se equivalem, sendo assim, o enfermeiro poderá estar prevenindo ocorrência das ITU's.
Behaviors assumed by nurses related to the vesical exploration proceedings
Conductas adoptadas por enfermeros relacionadas con el procedimiento de sondaje vesical
Keywords: Hospital infection; Vesicular probing; Procedures; Infección del hospital; Sondaje vesical; Procedimientos; Biológicas; Saúde; Infecção hospitalar; Sondagem vesical; Condutas